Tekniskt kunnande hos Sjöräddningssällskapets frivilliga - En studie om Sjöräddningssällskapets frivilliga och dess tekniska kunnande med avseende på Victoriaklassen - Modig, Karl; Larsson, Axel (My University, 2016)
The Swedish Sea Rescue Society is a Non-Governmental Organization that relies on volunteers to help save lives at sea. In the past, the Swedish Sea Rescue Society´s volunteers had vast experience with the sea and boats, while today they have grown as an organization where volunteers are not a homogeneous group and that the boats have become more technical. The Swedish Sea Rescue Society´s boat, the Victoria Class, which this thesis has been limited to is a very advanced boat seen from a technical perspective. The boat is developed with the purpose of lifesaving at sea. The purpose of the study is to investigate the technical knowledge to manage the operation and maintenance of the technical systems and how safe the volunteers feel to perform this. The questions that are answered in the thesis are what technical knowledge the volunteers have and if they feel comfortable to perform service and troubleshooting on the technical systems. The study was conducted as a quantitative case study, written in Swedish, in which survey methods have been used to reach out to the volunteers that man the boats. The results show weaknesses in education at the stations of the technical systems, and this is reflected in the level of knowledge that the volunteers have within these systems. The result also shows that there is a gap in the skills of some of those who have formal training as a marine engineer exam.
Keywords: Maskinteknik; Transport; Mechanical Engineering; Transport